Dynamic modeling and control of the SPIRAL2 cryomodules. (April 2019) - Vassal, A; Bonne, F; Ghribi, A; Millet, F; Bonnay, P; Bernaudin, P-E
Abstract: SPIRAL 2 (Caen, France) facility aims at delivering high intensity of rare isotope beams. The linear accelerator (LINAC) of the SPIRAL 2 facility is composed of 26 superconducting accelerating cavities distributed into 19 cryomodules cooled down with liquid helium at 4.4 K. A dynamic model of the cryomodules and their associated shields and valves thermodynamic behavior is proposed. This dynamic model is validated through comparisons between simulation and experimental data. Since the model is developed with the Simcryogenics library for MATLAB/Simulink environment, It is convenient for control loops design. Using the model, advanced control algorithms have been developed in order to achieve the cryomodule's pressure stability required for beam acceleration. This paper presents the dynamic model, experimental versus simulation results as well as the control outcome.